Synthesis and anticancer activities of novel 8-azapurine carbocyclic nucleoside hydrazones. Issue 20 (15th October 2015) - Wang, Yeming; Yan, Hong; Ma, Chao; Lu, Dan
Graphical abstract: IC50  = 11.69 μM (human liver cancer Huh-7 cell line). Abstract: A series of novel 8-azapurine carbocyclic nucleoside hydrazones were synthesized through a useful procedure starting from amino alcohol and pyrimido dichloride. All the products were characterized by 1 H NMR, 13 C NMR and HRMS spectral analysis and the stereochemical structure of key intermediate was also confirmed by a single crystal X-ray diffraction crystallographic analysis. Moreover, the anticancer activities were evaluated in vitro against human liver cancer Huh-7 cell line and human breast cancer A549 cell line.